Emotional Memory Formation Under Lower Versus Higher Stress Conditions - Kogan, Inna; Richter-Levin, Gal (Frontiers in Behavioral Neuroscience, 2010)
An exposure to stress can enhance memory for emotionally arousing experiences. The phenomenon is suggested to be amygdala-dependent and in accordance with that view the amygdala was found to modulate mnemonic processes in other brain regions. Previously, we illustrated increased amygdala activation and reduced activation of CA1 following spatial learning under high versus low emotionality conditions. When spatial learning was followed by reversal training interference, impaired retention was detected only under high emotionality conditions. Here we further evaluate the potential implications of the difference in the level of amygdala activation on the quality of the memory formed under these stress conditions. We attempted to affect spatial memory consolidation under low or high stress conditions by either introducing a foot shock interference following massed training in the water maze; by manipulating the threshold for acquisition employing either brief (3 trials) or full (12 trials) training sessions; or by employing a spaced training (over three days) rather than massed training protocol. The current findings reveal that under heightened emotionality, the process of consolidation seems to become less effective and more vulnerable to interference; however, when memory consolidation is not interrupted, retention is improved. These differential effects might underlie the complex interactions of stress, and, particularly, of traumatic stress with memory formation processes.